Ketidakmampuan CSR dalam Memoderasi Laporan Keuangan Terhadap Nilai Perusahaan Pada Indeks LQ45 - Yohana Patmita Putri; Tri Widianto (Excellent, 2026)
This study aims to analyze the effect of Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER) on firm value, with Corporate Social Responsibility (CSR) as a moderating variable. The population of this study consists of companies included in the LQ45 index. The research sample was selected using a purposive sampling method. The data used are secondary data obtained from companies’ financial statements and CSR data sourced from Refinitiv. The analytical methods employed are multiple linear regression and Moderated Regression Analysis (MRA) using the Statistical Package for the Social Sciences (SPSS). The results indicate that ROE has a significant effect on firm value, while CR and DER have no significant effect on firm value. Furthermore, CSR is not able to moderate the effect of ROE, CR, and DER on firm value.